Marketing in customer technology environments : prospective customers and magical worlds - Sudharshan, Devanathan (Emerald Publishing Limited, 2020)
New customer technology environments are magical worlds. With the rise of virtual reality, augmented reality, the internet of things and more, customers are more engaged, more involved, and easier to reach than ever ; while being inundated with increasing amounts of marketing material. How can you market effectively using these new CTEs? Providing an accessible description of these new, emerging technologies, along with novel frameworks with which to apply them, marketing expert Devanathan Sudharshan offers a straightforward guide to leveraging CTEs. Laden with examples to make the discussion vivid for readers and excite their imaginations, Sudharshan covers decision making in CTEs, mixed reality technologies and enabling technologies. CTEs are still emerging, and their business impact is yet to be measured. This exciting investigative text offers students, practitioners and researchers the chance to learn about these technologies, see the possibilities of their impacts, and their growing applications for the world.